PENGENALAN BISNIS DIGITAL DAN ASPEK HUKUM BISNIS UNTUK MENINGKATKAN MINAT KEWIRAUSAHAAN SISWA MAN 1 MERANGIN - Zulpa Adila; Ditya Putri Wulansari; Dede Iskandar (Hira Institute, 2025)
The Community Service Program (PKM) entitled “Introduction to Digital Business and Business Law to Enhance Entrepreneurial Interest of MAN 1 Merangin Students” aimed to improve students’ understanding of digital entrepreneurship and business legal aspects. Conducted at MAN 1 Merangin with 30 twelfth-grade students, the program employed structured material delivery, interactive discussions, and pre-test and post-test evaluations. The materials covered digital business concepts, technology-based business opportunities, and the importance of legal compliance in business. Results showed a significant improvement, with the average score rising from 54% in the pre-test to 89% in the post-test, representing an increase of approximately 65%. Students also demonstrated increased interest in digital entrepreneurship, reflected in their active participation throughout the program. These findings indicate that the program effectively enhanced students’ digital business literacy and legal awareness, strengthening their readiness to develop entrepreneurial activities aligned with technological and legal frameworks. This initiative contributes to fostering entrepreneurial competence and preparing students to adapt to the demands of the digital economy.